Aspergilloma complicating previous COVID‐19 pneumonitis – a case report. Issue 7 (16th May 2022) - Banke, Gry; Kjeldgaard, Peter; Shaker, Saher Burhan; Sivapalan, Pradeesh; Søholm, Jacob; Back Holmgaard, Dennis; Thyssen Astvad, Karen Marie; Bangsborg, Jette; Brun Andersen, Michael; Bonnesen, Barbara
Abstract : Aspergillomas are found in pre‐existing cavities in pulmonary parenchyma. To the best of our knowledge, aspergilloma has not previously been reported in COVID‐19‐associated pulmonary architecture distortion combined with barotrauma from invasive mechanical ventilation therapy. We present a case of a 67‐year‐old woman, who suffered from severe COVID‐19 in the summer of 2020 with no suspicion of infection with Aspergillus in the acute phase. Ten months after discharge from her COVID‐related admission, she developed bilateral aspergillomas diagnosed by image diagnostics, bronchoscopy, and blood samples, and she now receives antifungal therapy. We would like to raise awareness on aspergilloma in post‐COVID‐19 patients, since it is an expected long‐term complication to COVID‐19 patients with pulmonary architectural distortion.